Wnt Pathway: An Emerging Player in Vascular and Traumatic Mediated Brain Injuries - Menet, Romain; Lecordier, Sarah; ElAli, Ayman (Frontiers in Physiology, 2020)
Abstract The Wnt pathway, which comprises the canonical and non-canonical pathways, is an evolutionarily conserved pathway that regulates crucial biological aspects throughout the development and adulthood. Emergence and patterning of the nervous and vascular systems are intimately coordinated, a process in which Wnt pathway plays particularly important roles. In the brain, Wnt ligands activate a cell-specific surface receptor complex to induce intracellular signalling cascades regulating neurogenesis, synaptogenesis, neuronal plasticity, synaptic plasticity, angiogenesis, vascular stabilization, and inflammation. The Wnt pathway is tight regulated in the adult brain to maintain neurovascular functions. Historically, research in neuroscience has emphasized essentially on investigating the pathway in neurodegenerative disorders. Nonetheless, emerging findings have demonstrated that the pathway is deregulated in vascular- and traumatic-mediated brain injuries. These findings are suggesting that the pathway constitutes a promising target for the development of novel therapeutic protective and restorative interventions. Yet, targeting a complex multifunctional signal transduction pathway remains a major challenge. The review aims to summarize the current knowledge regarding the implication of Wnt pathway in the pathobiology of ischemic and haemorrhagic stroke, as well as in traumatic brain injury (TBI). Furthermore, the review will present the strategies used so far to manipulate the pathway for therapeutic purposes as to highlight potential future directions.